2016
DOI: 10.3168/jds.2015-10107
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Sensory profile and acceptability of a cow milk cheese manufactured by adding jenny milk

Abstract: The addition of jenny milk during cheesemaking has been recommended as a viable alternative to egg lysozyme for controlling late blowing defects. However, little is known on the sensory properties of the cheeses made with jenny milk. In this study, the effect of the addition of jenny milk during cheesemaking on sensory properties and consumer acceptability of cheese was evaluated. A sensory profile was carried out by 10 trained panelists on 4 cow milk cheese types. Two types of cheeses were made by adding jenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…The lower score may also be partially caused by the reduced whiteness of the product, as a consumer visual bias. This assumption could not be confirmed, even though sensory and acceptability trials have reported correlations between cheese colour and acceptability (Cosentino et al ).…”
Section: Discussionmentioning
confidence: 95%
“…The lower score may also be partially caused by the reduced whiteness of the product, as a consumer visual bias. This assumption could not be confirmed, even though sensory and acceptability trials have reported correlations between cheese colour and acceptability (Cosentino et al ).…”
Section: Discussionmentioning
confidence: 95%
“…The effect of sugar replacement with tagatose on the physico-chemical and sensory characteristics of low-sugar yogurt is yet to be studied. Indeed, a healthier yogurt alternative cannot outweigh its sensory qualities, and its acceptance is dependent on the degree of the consumers’ satisfaction [21,22]. An understanding of its functionality and its influence on consumers perception are critical for tagatose to successfully replace sugar in yogurt products.…”
Section: Introductionmentioning
confidence: 99%
“…Hexanoic acid originated from lipolysis and was responsible for the creation of the cheesy and pungent aroma in cheeses. Its presence was also reported in the VCs identified in a type of semi‐hard cheese produced by adding different aliquots of jenny milk to cow milk (Cosentino et al., 2016) and an Italian PDO sheep cheese (Urgeghe et al., 2012). Previous studies indicated that microbial originated acids were more dominant at the end of the ripening period, while those produced by lipolysis reactions were maximized at the first stage of ripening (Delgado et al., 2010).…”
Section: Resultsmentioning
confidence: 69%